Connexin 43 dephosphorylation mediates the Dchs1/YAP/TEAD signaling pathway to induce cardiac fibrosis - Wang, Min; Li, Wanning; Shao, Yaqing; Wang, Feng; Huang, Ying; Wei, Chenchen; Li, Ping; Sun, Kangyun; Yan, Xinxin; Gou, Zhongshan (Biochimica et biophysica acta. Molecular cell research, 2025)
Background - The gap junction protein connexin 43 (Cx43) has been implicated in the development of cardiac fibrosis. Our previous findings revealed that Cx43 dephosphorylation at serine 282 (S282) is related to cardiomyocyte apoptosis and arrhythmias in hearts damaged by ischemia/reperfusion. In this study, we investigated the role of Cx43 S282 phosphorylation in cardiac fibrosis. - Methods - We used angiotensin II (Ang II) intervention in mice to establish an in vivo cardiac fibrosis model and transforming growth factor β-1 (TGF-β1) intervention in cardiac myofibroblasts to establish an in vitro fibrosis model. The expression of Cx43 S282 phosphorylation was examined in the in vivo and in vitro models. To further confirm the effect of Cx43 S282 phosphorylation on cardiac fibrosis, we transfected cardiac myofibroblasts with lentiviral bodies in vitro, and injected myocardium with adenovirus in vivo to establish the over-expression of phosphorylation of Cx43 S282 locus and mutant groups. We sequenced the mRNA of the in vitro group using gene set enrichment analysis (GSEA) and normalized enrichment scoring (NES) to investigate the signaling pathway by which p282-Cx43 affects myocardial fibrosis (MF). The role of the Hippo signaling pathway in phosphorylation at the Cx43 282 site was further validated. - Results - In an in vivo and in vitro model of cardiac fibrosis, the level of phosphorylation of Cx43 S282 was reduced. Mutation of Cx43 S282 to a less phosphorylatable form (S282A) resulted in elevated levels of fibrosis markers, suggesting a critical antifibrotic role for phosphorylated Cx43 S282. Increased phosphorylation of Cx43 S282 produced an inhibitory effect on fibrosis. Enrichment analysis of mRNA sequencing in the mutant model group indicated that the Hippo signaling pathway was involved in the fibrosis process. Cx43 S282 phosphorylation increased the expression of Dchs1 gene, which activates the phosphorylation of yes-associated protein (YAP) and inhibits the YAP/TEAD signaling pathway to inhibit fibrosis development. - Conclusions - This study suggests that the phosphorylation of Cx43 S282 could be an effective antifibrotic target in cardiac fibroblasts. This indicates a novel mechanism and a molecular target that may hold promise for treating cardiac fibrosis.
Online verfügbar: 10. Februar 2025, Artikelversion: 16. Februar 2025
Gesehen am 16.06.2025